2010
DOI: 10.1097/rli.0b013e3181c8cf19
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Interstitial CT Lymphography Using Optimized Iodized Oil Emulsion in Rats

Abstract: Iodized oil emulsion made with a surfactant mixture (Tween 80 as the main surfactant and TPGS, Kollidon 12 PF, or Span 85 as the cosurfactant) provided sufficient and sustained contrast enhancement on CT of targeted lymph nodes with washout on delayed phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Particles in the size range of 10-200 nm have been known to be more effective for sentinel node detection [28,29]. In our previous report, we demonstrated that iodized oil emulsion made with a surfactant mixture provided sufficient and sustained contrast enhancement on CT of targeted LNs in rat models through the optimization of particle size (approximately 120-130 nm) [18]. Therefore, we applied this agent for SLN detection using endoscopic injection into the canine stomach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particles in the size range of 10-200 nm have been known to be more effective for sentinel node detection [28,29]. In our previous report, we demonstrated that iodized oil emulsion made with a surfactant mixture provided sufficient and sustained contrast enhancement on CT of targeted LNs in rat models through the optimization of particle size (approximately 120-130 nm) [18]. Therefore, we applied this agent for SLN detection using endoscopic injection into the canine stomach.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the particulate nanoscale iodized oil emulsion have been described previously [18]. In brief, polyoxyethylene sorbitan monooleate (Tween 80) and sorbitan trioleate (Span 85) were purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Preparation Of Particulate Iodized Oil Emulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, surgical reinterventions are associated with a significantly higher morbidity. Using iodized oil for lymphography as contrast agent, this substance has the potential to induce granulomatous reactions when extravasating [4,5] which may be further assisted by additive conservative measures [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Contrast-enhanced sonography can survey only to a limited depth from the detector, and so, it is not suitable for detecting the deep lymphatic system. CT lymphography using water-soluble, nanoparticulate, iodine contrast, oil-in-water emulsion has been reported as a feasible method to detect lymph nodes with high resolution images.…”
Section: Introductionmentioning
confidence: 99%